Not One of Those Girls: An existential-phenomenological exploration of my eyeliner (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This is a phenomenological exploration of my relationship with eyeliner. I draw parallels between the loss of possibilities in Heidegger's being-towards-death and the cutting off of the possibility of wearing eyeliner through illness. I discuss Sartrean and Kierkegaardian views of the self and how, through illness, self can become Other.
Keywords: Self; other; illness; cosmetics; ritual; being-towards-death; meaninglessness